Assessing the temporal distribution of dengue vectors mosquitoes and its relationship with weather variables - Masnita Md Yusof,; Nazri Che Dom,; Rodziah Ismail,; Ariza Zainuddin, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Dengue fever is a vector-borne disease. The infectious disease is often transmitted by mosquito namely Aedes species. Understanding of Aedes mosquito abundance is essential to plan comprehensive control activities. A cross-sectional study was conducted in Jempol Negeri Sembilan, Malaysia. A total of 960 ovitraps were deployed at Taman Satelite and Felda Raja Alias 4 from April to September 2017 biweekly. These localities were divided to two different setting, which are vegetative and populated environments. This study aims to assess, first, the distribution and abundance of Aedes species by measuring two variables which are positive ovitrap index (POI) and mean eggs per ovitraps (MET) in populated and vegetative environments. Thus, ANOVA was used as a statistical analysis in order to determine the difference of POI and MET in difference environment. Second, Aedes species was identified to show the index ratio between Aedes aegypti and Aedes albopictus. And lastly, correlation between POI and MET with weather data in order to determine the relationship between Aedes distribution and abundance with temperature, humidity and rainfall. Beside, Pearson and Spearman coefficient correlation were used to determine the correlation. From the total ovitrap, 945 (98.44%) were inspected with 428 (45.29) were identified positive. A total of 9929 eggs were collected during study session. The highest POI at Felda Raja Alias 4 at vegetative environments was 85%, while populated environment stated the highest POI with 75%. Aedes distributions in Raja Alias 4 was significantly higher in vegetative environment compared to populated environment (p= 0.048). In Taman Satelite, highest POI in vegetative environment was 50%, while highest POI in populated environment was 45%, therefore significantly, Aedes distribution in vegetative environment was higher than populated environment (p=0.039). For Aedes abundance, the highest MET at Felda Raja Alias 4 at vegetative environment was 50.50 compared to populated environment with 30.13. In Taman Satelite, vegetative environment stated highest MET with 47.38 and populated environment stated highest MET with 42.50. Overall species ratio of Aedes aegypti and A. albopictus was 1:39. Aedes albopictus is a dominant species in this study compared to A. aegypti. Positive correlation between POI and temperature was determined (r= 0.022, p-value= 0.88). The distribution of Aedes mosquito were higher when temperature was arising conversely when humidity and rainfall were decreased. In contrast, POI was negatively correlated with humidity (r= -0.229, p-value= 0.09) and rainfall (r= -0.153, p-value= 0.51). However, the abundance (MET) of Aedes mosquito shown a negative correlation with weather variables where the correlated with temperature (r= 0.091, p-value= 0.41), humidity (r= -0.240, p-value= 0.87) and rainfall (r= -0.209, p-value= 0.73). The abundance of Aedes mosquito was higher at lower temperature, humidity and rainfall. As for conclusion, Aedes mosquito distribution will arise with high temperature and decrease of humidity and rainfall, thus, Aedes mosquito abundance will arise at lower temperature, humidity and rainfall. Aedes vectors tend to be vegetative than populated environment, however, populated environment still presence the Aedes vectors. This study should be conducted in another geographical condition of localities to create a baseline data and comprehensive dengue management.